Prevalence of partial edentulism among the patients visiting a Tertiary Health Care Center in the Western Region, Nepal - Manandhar, Pratik; Ranjit, Rebicca; Tuladhar, Sapna Laxmi; Bhandari, Arjun (Journal of Gandaki Medical College-Nepal, 2021)
Introduction: Tooth loss causes impairment, functional limitation, physical, psychological, and social disability.  Hence, the study of pattern of tooth loss can provide a rough information about the frequency, cause and magnitude of oral problems, its sequelae that eventually can act as mirror image of prosthodontic treatment needs. Objectives: To assess the prevalence of partial edentulism and its etiology, to determine its association with sociodemographic parameters, and to find out the motivational factor/s for replacement in willing patients.Methods: Total 417 patients with partial edentulism were examined intraorally on the basis of Kennedy’s classification with Applegate’s modification. The descriptive analysis was done using frequency distribution. Pearson Chi-square analysis test was used to determine the association between demographic variables and type of tooth loss where p-value ≤0.05 was considered statistically significant.Results: Partial edentulism was more prevalent in mandibular arch (41.7%) followed by both arches (30.9%). Kennedy’s Class III was the commonest and Kennedy’s class III modification 1 was second most common type of partial edentulism. Age and educational status had statistically significant association while gender had no association with various classes of partial edentulism. Dental caries (62.8%) followed by periodontitis (25.9%) were the major causes of tooth loss. Functional demand (46.8%) was the key motivational factor for the replacement among those who were willing (78.4%).Conclusions: This study can help in assessing the epidemiological features of partial edentulism of one community in a more classified form and can help gather information necessary to assess the treatment needs.